Analisis Kesulitan Belajar Dalam Mata Kuliah Analisis Kompleks Ditinjau Dari Kemandirian Belajar Mahasiswa - Nasifatul Ulya; Aryani Indri Arsani; Nur Salsabila; Umi Mahmudah (Lembag, 2024)
Tadris Mathematics students have difficulty understanding complex analysis courses when studying independently because many students still lack confidence in doing assignments and only rely on help from others. Learning difficulties greatly affect learning independence. This study aims to determine the level of difficulty in learning complex analysis based on students' learning independence. The research method used in this research is descriptive with a qualitative approach. The data collection technique used was purposive sampling by distributing questionnaires in the form of google forms given to 20 students of the Tadris Mathematics study program at UIN K.H Abdurrahman Wahid Pekalongan. Then the researcher conducted interviews with three students as representatives of classes A, B, C. The results of the study show that in general, Tadris Mathematics students have learning difficulties based on independence and difficulty understanding language in complex analysis courses. This learning independence can create students' ability to control and organize themselves in carrying out learning activities.